Interior Design of Purwa Caraka Music Studio in Surakarta - Sintang Mahardikawati Malag; Ahmad Fajar Ariyanto (Pendhapa, 2021)
Purwa Caraka Music Studio is an informal music school that is quite well known in Indonesia, which has 90 branches; one of them is in Surakarta. The Interior Design of Purwa Caraka Music Studio in Surakarta aims to fulfil the users’ activities to be comfortable and safe by implementing health protocols during the pandemic. This design applies the theme rhythm with a contemporary pop art style. Batik Parang Tuding motif is used as a design transformation because it shares the same meaning as Purwa Caraka Music Studio's vision "we teach music better". The design method uses the method of Pamudji Suptandar with data sources from informants, literature, and photos/objects/artefacts. Data collection techniques use structured interview techniques, literature study, and observation